Histopathological and diagnostic study of Toxoplasmosis in human and sheep by using ELISA in Kut city: Alaa M. N. Al-Khafagi and Zainab, R. Zghair - Zghair, Zainab R. (The Iraqi Journal of Veterinary Medicine, 2017)
This study is designed to diagnosis blood Toxoplasmosis in human (women and men) and sheep (male and female) by using Elisa test; as well histopathological examination of heart, liver and lung of sheep were also done, internal organs were also obtained heart, liver and lung. Women diagnosis was performed by collection 96 samples from aborted women ageing from 15-45 years and divided into three groups; first group 15-25 years involved 50 sample, second group 25-35 years include 37 samples; and the third group 35-45 years included 9 samples. The results of Elisa test showed six positive of IgG, (two for each group) and one positive IgM for the second group, a significant (P<0.05) difference in the first and third groups between IgG and IgM was found. The total percentage of the infection 4, 8.1and 22.2 for the first, second and third groups respectively, and Total of 96 blood samples were collected from men with different chronic diseases and were divided into four groups, (first, second and third) each containing 25 samples and suffering from Thalasemia, renal failure and cancer respectively; of them 21 samples collected from normal men as fourth control group. The results of Elisa diagnostic test indicated 9, 9, 7 and 2 positive of IgG for first, second, third and fourth groups respectively, and 1, 2, 0 and 1 positive of IgM. The total percentage of Toxoplasmosis infection 38.4, 44, 28 and 14.28 for the first, second, third and fourth groups respectively, with a difference between them except the second group appeared significantly P(0.05). 92 samples of sheep blood were collected from male 46 and 46 female. The results of Toxoplasmosis showed one case positive IgG for female and one for male only. The histopathological examination of sheep positive case with chronic infection revealed pathological changes in the organs, the heart showed multiple variable sizes of parasite cysts embedded and scatter between cardiac muscle fibers, in addition to aggregation of inflammatory cells around the blood vessels forming nests of inflammatory cells with congestion of blood vessels in liver and lung. In conclusion that the infection with Toxoplasmosis in Kut city revealed the percentage of infection in men more than the aborted women, also it reported few cases of infection in sheep.